HUBUNGAN PENGETAHUAN DAN PENDIDIKAN AKSEPTOR KB TERHADAP PENGGUNAAN ALAT KONTRASEPSI IUD DI UPTD PUSKESMAS WOLO KECAMATAN WOLO KABUPATEN KOLAKA - Kasmawati Kasmawati; Jumrana Jumrana (Lembaga Pengembangan Kinerja Dosen, 2022)
The percentage of contraceptive users in Indonesia who use contraceptive methods reaches 61.4%. The largest pattern of contraceptive use is injections at 31.6%, pills at 13.2%, IUDs at 4.8%, implants at 6.8%, condoms at 1.3%, MOW at 0.3%, MOP at 0, 2%. Based on BKKBN data from Bone Regency, South Sulawesi Province, the number of active IUD type family planning participants is 5.5%. At the Biru Community Health Center, data was obtained on family planning acceptors in December 2015, namely, as many as 2517 injectable family planning acceptors, 945 implant birth control acceptors, 1624 pill birth control acceptors, and 779 IUD contraceptive acceptor. The use of IUD contraception is still very far from the target set at 80%. For this reason, the aim of this research is to determine the relationship between knowledge and education of family planning acceptors and the use of IUD contraception.The type of research used is quantitative. The research design used in this study used an analytical survey with a cross-sectional time approach.